أهداف الولايات المتحدة الأمريكية وإستراتيجيتها في منطقة الخليج العربي - إسماعيل عصام; سويد عمار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research confirms the great importance of the Gulf region for the United States of America and the permanent attempt to keep its countries under American hegemony. The research reviews the history of US-Gulf relations through lighting on the most important historical periods in these periods, especially since the beginning of the American military presence and the subsequent discovery of oil , To the oil crisis and through the aftermath of the first Gulf wars and the second and after the events of atheist of September to the present time. The research focuses on the fixed objectives of the US policies in the Gulf region through dividing them into political and economic objectives and protecting the security of the Zionist entity, as well as the change in the policies pursued by the United States in terms of economic ties, political projects and direct military interventions. The research yielded many results and made some recommendations. يؤكد هذا البحث على الأهمية الكبيرة لمنطقة الخليج العربي بالنسبة للولايات المتحدة الأمريكية والمحاولة الدائمة لإبقاء دولها تحت الهيمنة الأمريكية، ويستعرض البحث تاريخ العلاقات الأمريكية الخليجية من خلال الإضاءة على أهم الفترات التاريخية التي مرت بها هذه العلاقات وخاصة منذ بداية التواجد العسكري الأمريكي وما تلاه من اكتشاف النفط، وصولاً للأزمة النفطية ومروراً بما تلاها من حروب الخليج الأولى والثانية وما بعد أحداث الحادي عشر من أيلول وحتى وقتنا الحالي، ويركز البحث على الأهداف التي تقوم عليها السياسات الأمريكية في منطقة الخليج من خلال تقسيمها إلى أهداف سياسية واقتصادية وحماية أمن الكيان الصهيوني، كما يشير إلى التغير في السياسات التي تتبعها الولايات المتحدة من ناحية الارتباطات الاقتصادية والمشاريع السياسية والتدخلات العسكرية المباشرة وتأجيج الصراعات البينية والإقليمية. وتوصل البحث إلى العديد من النتائج، وقدم بعض التوصيات.